Implications of new technologies on consumer engagement - Ajayi, S.; Loureiro, S. M, C.; Langaro, D. (Proceedings of AIRSI 2022: Technologies 4.0 in tourism, service and marketing, 2022)
New technologies will continue to create added values to companies that adapt, as it gives a competitive advantage that significantly influences consumer behavior (Rangaswamy et al., 2020). The customer’s willingness to patronize the services of companies with the internet of things (IoT hereafter) enabled services through electronic channels gives the customer the ‘control’ over the business relationship with the company (Johnson, 2007). The concept of IoT has attracted a lot of attention, largely attributed to its importance due to its considerable internalization in our daily lives (Libai et al., 2020). Consumer engagement (CE hereafter), on the other hand, has equally gained some attention in recent times due to the dynamism in the academic, retail, business (Pansari and Kumar 2017) and practitioners’ landscape (Dessart et al., 2017). With the advent of IoT, there has been a significant shift from human-to-human, human-to-machine, or machine-to-machine interactions (Bulmer et al., 2018).